2020
DOI: 10.1097/md.0000000000023151
|View full text |Cite
|
Sign up to set email alerts
|

Platelets as a prognostic marker for sepsis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Due to limited treatment methods, early identification and early intervention are the key to the treatment of sepsis 25 . Previous studies have investigated the predictive performance of several biomarkers in the prognosis of sepsis patients, including platelet 26 , neutrophil/lymphocyte ratio (NLR) 27 , lactate/albumin ratio 28 , plasminogen activator inhibitor-1 (PAI-1) 29 , signal peptide-CUB-epidermal growth factor-like domain-containing protein 1 (SCUBE-1) 30 , and vitamin D receptor 31 . CAR has been recently used as a new prognostic marker in COVID-19 32 , severe fever with thrombocytopenia syndrome (SFTS) 33 , and cardiac arrest 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited treatment methods, early identification and early intervention are the key to the treatment of sepsis 25 . Previous studies have investigated the predictive performance of several biomarkers in the prognosis of sepsis patients, including platelet 26 , neutrophil/lymphocyte ratio (NLR) 27 , lactate/albumin ratio 28 , plasminogen activator inhibitor-1 (PAI-1) 29 , signal peptide-CUB-epidermal growth factor-like domain-containing protein 1 (SCUBE-1) 30 , and vitamin D receptor 31 . CAR has been recently used as a new prognostic marker in COVID-19 32 , severe fever with thrombocytopenia syndrome (SFTS) 33 , and cardiac arrest 34 .…”
Section: Discussionmentioning
confidence: 99%
“…INR is also an effective sepsis screening indicator and prognostic factor ( 53 , 54 ). During the initial stages of infection, coagulation acts as a natural defense mechanism in an attempt to limit the pathogen and prevent its spread to systemic circulation ( 48 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of researchers have found that inflammatory biomarkers, such as ALB [ 17 ], ferritin [ 6 ], Albumin/Fibrinogen [ 18 , 19 ], hematocrit [ 20 ], platelets [ 21 ], Red blood cell distribution width [ 22 ], systemic immune-inflammation index [ 23 ], Prognostic nutrition index [ 24 ], and urea nitrogen/albumin [ 25 ], etc. FAR holds potential as a prognostic indicator for predicting the outcome of sepsis patients.…”
Section: Discussionmentioning
confidence: 99%